Deforestation changes the effectiveness of bed nets for malaria control - Tafesse Kefyalew Estifanos; Brendan Fisher; Taylor H. Ricketts (People and Nature)
Abstract Land use changes such as deforestation and the degradation of tropical forests can be key drivers of infectious disease, including malaria. However, programmes that evaluate the effectiveness of malaria‐control strategies such as bed nets rarely account for the impacts of surrounding land use change. This study investigates how the cumulative deforestation rate for nearly 20 years moderates the effectiveness of bed nets on malaria positivity in children under age of 5 years. We used multilevel mixed‐effect modelling, demographic and health data, and remotely sensed environmental data to analyse malaria positivity among 18,610 children in six malaria‐endemic sub‐Saharan African countries. Our models suggest that deforestation is positively associated with increased odds of malaria positivity, whereas bed net use is negatively associated with malaria positivity, as expected. However, we also found that the effectiveness of bed net use varies with the extent of deforestation levels. Bed net use is associated with a significant reduction (by 24.7% to 32%) in malaria positivity at sites with less than 50% deforestation, but this effect is not observed at sites where deforestation exceeded 50%. Our findings suggest that the extent of deforestation can influence the efficacy of malaria control interventions, highlighting the need to integrate deforestation and malaria control considerations when designing environmental conservation and public health policies. Read the free Plain Language Summary for this article on the Journal blog.